PENINGKATAN LITERASI DAN NUMERASI BAGI SISWA SMP ST. AGUSTINUS LANGA MELALUI PROGRAM KAMPUS MENGAJAR - Maria Vianney Iju; Ngurah Mahendra Dinatha (LPPM Universitas Muhammadiyah Bulukumba, 2024)
Literacy and numeracy skills in Indonesia are currently still quite low and still need to be improved in order to achieve national education goals, namely to make the nation's life smarter. One of the efforts being made to improve students' literacy and numeracy skills is through the current government program, namely the campus teaching program. Student service at school for approximately 6 months aims to improve the literacy and numeracy skills of students at St. Agustinus Langa through the implementation of the Independent Campus Learning Program. Through a naturalistic qualitative approach, data is obtained through observation, interviews and documentation. The results of this research show that the level of literacy and numeracy is still low at St. technology. The importance of literacy and numeracy is not only limited to Mathematics and Science subjects but includes other aspects that enable students to analyze information, make predictions, design experiments or experiments and make decisions.